(untitled) (Research, Society and Development, 2021)
During the dry season, the water deficit makes the grasses have low quality, in addition to reducing the supply of this forage, thus, silage is an alternative, as it preserves forage, to feed the animals during this period. The aim of this study was to evaluate elephant grass silages with acai residue on sensory characteristics, fermentation pattern, aerobic stability and chemical-bromatological composition. The treatments consisted of elephant grass silage with inclusion of 0 and 15% of residue in the natural matter, with 5 repetitions. The grass came from UFOPA’s Experimental Farm. The açaí residue was collected at 4 different points of sale (Natureza, Tapajós, Nativo and Alemão). The mean pH value of the silages was 3.86. The average temperature of the treatments was 24.35°C. Silage without the addition of açaí had lower dry matter content (247.82 g/kg). Silage without açaí residue had lower NDF content (631.24 g/kg). The treatment with addition of residue from Açaí Nativo showed higher CP content (70.42 g/kg) compared to Nature silage (58.62). As for ammonia nitrogen, the Tapajós treatment had the highest content (3.6%). Silages without the addition of açaí and Alemão remained stable during the period of exposure to air. It is concluded that the addition of 15% of açaí residue to elephant grass for ensiling maintains the sensory characteristics of silages of good nutritional quality, increases the DM and NDF contents and reduces the MM. Elephant grass and Alemão silage showed better aerobic stability.